Influence of exercise on autonomic nervous system and sleep - Stanić, Ivan; Smoljo, Tomislav; Barun, Barbara; Habek, Mario (Medicinski podmladak, 2018)
Physical activity changes our body in many aspects, including autonomic regulation of cardiovascular system and thermoregulation, changes in metabolism, secretion of hormones and, as a consequence, mental changes. Acute effect of physical effort is increased sympathetic activity leading to condition known as fight or flight which, includes tachycardia, tachypnea, blood pressure increasement, pupil dilatation and increased attention. Parasympathetic activity is increased between series of trainings, during the resting state, and its effect is often referred to as rest and digest state. It includes increased salivation, drop in heart rate, bronchoconstriction, myorelaxation and pupil constriction. There are other factors responsible for the influence of exercise on our body. Good feelings and better memory after exercise are caused by secretion of various compounds, such as BDNF, dopamine and endorphins as well as blood flow, leading to the use of exercise as therapeutic method but also as an agent of addiction. Sleeping is also altered by physical activity directly through nervous system and indirectly through metabolism and hormones. There are various types, aerobic and resistance, and frequencies of physical activity that can be used as treatment of many disorders and states. In this article we will discuss multiple benefits of resistance training on autonomic nervous system function and sleep.